IMPLEMENTASI CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED SPECIES OF WILD FAUNA AND FLORA 1973 TERHADAP PERLINDUNGAN HEWAN TARSIUS FUSCUS DI TAMAN NASIONAL BANTIMURUNG BULUSARAUNG KABUPATEN MAROS: IMPLEMENTATION OF CONVENTION ON INTERNATIONAL TRADE IN ENDANGERED 1973 SPECIES OF WILD FAUNA AND FLORA ON PROTECTION TARSIUS FUSCUS IN BANTIMURUNG NATIONAL PARK BULUSARAUNG, MAROS REGENCY - Siti Anggur, Beby Ais; A. Hasan, Yulia; Oner, Basri (Clavia, 2021)
The aims of the research are to investigate: Implementation of the 1973 Convention onInternational Trade in Endangered Species of Wild Fauna and Flora against the protection oftarsius fuscus; Legal action to be taken by the Government of Maros Regency againstperpetrators who hunt and trade tarsius fuscus which is classified as a protected animal.The research method used is Normative Empirical research located in Maros Regency andMakassar City. Data collection techniques through literature and interviews. The results of thestudy; 1) Implementation of the 1973 Convention on International Trades in EndangeredSpecies of Wild Flora and Fauna on the protection of the tarsier fuscus animal in theBantimurung Bulusaraung National Park, Maros Regency, has been implemented nationally,but the real implementation in the community is still not implemented optimally because theabsence of the formation of regional regulations which in this case can be a pillar to reach thecommunity to the fullest. 2) The legal action given by the Government of Maros Regency to theperpetrators of burial and trafficking is in the form of a criminal sanction of five years in prisonand an administrative sanction in the form of a fine or a warning letter.